2012
DOI: 10.3109/00365521.2012.694901
|View full text |Cite
|
Sign up to set email alerts
|

Serum FGF21 and RBP4 levels in patients with chronic hepatitis C

Abstract: Serum FGF21 levels increased in CHC patients, especially in those with steatosis and were associated with steatosis grade. FGF21 seems to be a useful diagnostic marker in determining hepatic steatosis in CHC. A negative association between serum RBP4 and necro-inflammatory activity indicates that disease severity may determine RBP4 levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 43 publications
4
14
1
Order By: Relevance
“…In HCV infected patients, studies showed that both mRNA levels of PPAR-a and FGF21 were downregulated with a concomitant elevation in the level of HCV RNA [13]. However, in another cross-sectional study, serum FGF21 level suggested a positive correlation with steatosis grade in chronic hepatitis C patients [66]. Given FGF21 elevation in the subjects with hepatic steatosis could induce several liver diseases aforementioned, it is possible that FGF21 is increased in HCV.…”
Section: Fgf21 In Viral Hepatitismentioning
confidence: 95%
See 1 more Smart Citation
“…In HCV infected patients, studies showed that both mRNA levels of PPAR-a and FGF21 were downregulated with a concomitant elevation in the level of HCV RNA [13]. However, in another cross-sectional study, serum FGF21 level suggested a positive correlation with steatosis grade in chronic hepatitis C patients [66]. Given FGF21 elevation in the subjects with hepatic steatosis could induce several liver diseases aforementioned, it is possible that FGF21 is increased in HCV.…”
Section: Fgf21 In Viral Hepatitismentioning
confidence: 95%
“…HCV infection may correlate with FGF21 expression [13,66]. In HCV infected patients, studies showed that both mRNA levels of PPAR-a and FGF21 were downregulated with a concomitant elevation in the level of HCV RNA [13].…”
Section: Fgf21 In Viral Hepatitismentioning
confidence: 99%
“…However, another study by Kukla et al . did not confirm these observations in CHC [92]. Further investigations involving a larger number of patients are required to better determine the exact role of novel adipokines in CHC.…”
Section: Molecular Mechanisms Of Hcv-induced Insulin Resistancementioning
confidence: 99%
“…Moreover, IR is a strong predictor of poor response to antiviral therapy, alongside advanced hepatic steatosis and fibrosis [6,14]. Numerous reports have demonstrated altered levels of some adipokines such as leptin, adiponectin, resistin, visfatin, vaspin, chemerin and fibroblast growth factor (FGF) 21 in CHC patients [4,15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%